Beneath the surface : my story - Phelps, Michael, 1985-; Cazeneuve, Brian (New York : Sports Publishing, 2012)
In this candid memoir, Phelps talks openly about his battle with attention deficit disorder, the trauma of his parents<U+2019> divorce, and the challenges that come with being thrust into the limelight. Readers worldwide will relive all the heart-stopping glory as Phelps completes his journey from the youngest man to ever set a world swimming record in 2001, to an Olympic powerhouse in 2008, and the most decorated Olympian in 2012. Athletes and fans alike will be fascinated by insights into Phelps<U+2019> training, mental preparation, and behind-the-scenes perspective on international athletic competitions. A chronicle of Phelps<U+2019> evolution from awkward teenager to media-savvy superstar, Beneath the Surface is a must-read for any sports fan.
Keywords: Phelps, Michael, -- 1985-; Swimmers -- United States -- Biography